Development and Deployment of High Yielding Rust Resistant Wheat Varieties in India – Insights from Technology Transfer and Policy Response from the National Seed Production Program: Development and Deployment of Wheat Varieties in India - Sendhil, Ramadas; Amit Kumar Sharma; Raj Kumar; Chandra Nath Mishra; Anuj Kumar; Satyavir Singh; Gyanendra Pratap Singh (Journal of Cereal Research, 2023)
Wheat, a major Indian staple food crop, is largely prone to rust infection. Inter alia, wheat producers have been advocated to adopt the recently released high yielding rust resistant wheat varieties to counter the significant yield losses. In the milieu, we investigated the technological trend in seed indent followed by policy options for the transfer of technology at farmers’ fields. Research findings indicated that the wheat producers adopted old varieties. In the recent past five years, the trend hasn’t witnessed any drastic change despite several rust-resistant varieties having been tested and released for various agro-climatic conditions. Recent varieties take about 5 years to reach their peak adoption since release which is attributed to the innovative transfer of technologies. At the producers’ level, technologies (varieties) have been upscaled through frontline demonstrations, especially in cluster mode. Demonstrations resulted in an average yield gain of 699 kg/ha for innovative rust-resistant technology (HD 2967) compared to its check. Despite the increasing demand and promotion of the latest technologies, the need and availability of ‘producer choice variety’ is persisting and has to be addressed. Innovations like ‘community seed banks’, strengthening public-private partnerships, contract farming (quadpartite model), participatory demonstrations, and blockchain-enabled ‘seed tracker’ will strengthen the transfer of technology system in Indian wheat production.